FRASA NOMINA DALAM TUGAS LAPORAN OBSERVASI SISWA KELAS X MIPA 7 SMA NEGERI 1KOTA JAMBI - Berlianti Eka Sukma; Abdoel Ghafar; Supriyati Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research aims at describing the noun phrase which is occured in students’ observation report of X MIPA 7 class at SMA Negeri 1 Jambi city academic year 2020/2021 which consisted of modifying, coordinating, and opposite noun phrase. This research is qualitative descriptive which means a research which describes particular event with words or the situation of the subject which appears in certain environment or situation. From the results of the research, it can be described that there are three kinds of noun phrase occured in students’ observation report, they are; modifying, coordinating, and opposite noun phrase. There are 63 types of modifying noun phrase and 21 types of coordinating noun phrase. Opposite noun phrase does not found in their observation report. The most dominant noun phrase occured is modifying noun phrase and the less is opposite noun phrase. From the analysis, it can be concluded that the phrase which are occured in students’ observation report of X MIPA 7 class of SMA Negeri 1 Jambi city academic year 2020/2021 are modifying, coordinating, and opposite noun phrase.